The effects of bilateral posterior parietal cortex tRNS on reading performance. (6th November 2022) - Bertoni, Sara; Franceschini, Sandro; Campana, Gianluca; Facoetti, Andrea
Abstract: According to established cognitive neuroscience knowledge based on studies on disabled and typically developing readers, reading is based on a dual-stream model in which a phonological-dorsal stream (left temporo-parietal and inferior frontal areas) processes unfamiliar words and pseudowords, whereas an orthographic-ventral stream (left occipito-temporal and inferior frontal areas) processes known words. However, correlational neuroimaging, causal longitudinal, training, and pharmacological studies have suggested the critical role of visuo-spatial attention in reading development. In a double blind, crossover within-subjects experiment, we manipulated the neuromodulatory effect of a short-term bilateral stimulation of posterior parietal cortex (PPC) by using active and sham tRNS during reading tasks in a large sample of young adults. In contrast to the dual-stream model predicting either no effect or a selective effect on the stimulated phonological-dorsal stream (as well as to a general multisensory effect on both reading streams), we found that only word-reading performance improved after active bilateral PPC tRNS. These findings demonstrate a direct neural connectivity between the PPC, controlling visuo-spatial attention, and the ventral stream for visual word recognition. These results support a neurobiological model of reading where performance of the orthographic-ventral stream is boosted by an efficient deployment of visuo-spatial attention from bilateral PPC stimulation.